Public Administration - Smih, Kevin B (Roxbury Publishing. Company, 2006)
Includes bibliographical references; Public Administration: Power and Politics in the Fourth Branch of Government presents public administration through the lens of politics and the policy-making power of the bureaucracy. By showing how the bureaucracy influences daily life, Smith and Licari bring the field of public administration alive for students. This text dispels the myth that the study of public administration is boring or irrelevant to students' lives by demonstrating just how deeply it pervades our lives. The authors focus on the bureaucracy--"the fourth branch of government"--as a key ingredient in politics and policy-making. This approach is novel, but it accurately reflects the true nature of public administration in America. This book examines our bureaucracy's considerable political power, where it comes from, how it is used, and how it can be controlled